2019
DOI: 10.1089/soro.2018.0110
|View full text |Cite
|
Sign up to set email alerts
|

Sensorized, Flat, Pneumatic Artificial Muscle Embedded with Biomimetic Microfluidic Sensors for Proprioceptive Feedback

Abstract: In recent years, soft components, such as pneumatic artificial muscles (PAMs), have been increasingly employed to design safer wearable devices. Despite the inherent compliance of the materials used to fabricate PAMs, the actuators are able to produce relatively large forces and work when compared to their weight. However, effective operation of these systems has traditionally required bulky external force and position sensors, which limit the maneuverability of users. To overcome these issues, inspiration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…The use of soft tactile sensors for closed-loop control is still in its nascency. The few relevant studies in this area use low-dimensional soft strain sensors for closed-loop kinematic or force control (76,120,121). This is surprising given the wealth of literature on soft sensing technologies and considering the intended application of these sensors (32).…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…The use of soft tactile sensors for closed-loop control is still in its nascency. The few relevant studies in this area use low-dimensional soft strain sensors for closed-loop kinematic or force control (76,120,121). This is surprising given the wealth of literature on soft sensing technologies and considering the intended application of these sensors (32).…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…Pneumatic artificial muscles have been increasingly investigated owing to the potential in wearable devices. Inspired by biological muscle, Jackson et al designed an artificial muscle with both force and position sensors [137], as shown in Figure 11A. The Golgi tendon organ and muscle spindle were fabricated by EGaIn.…”
Section: Pneumatic Artificial Musclesmentioning
confidence: 99%
“…[136]. (B) The sensorized, flat, pneumatic artificial muscle at rest and inflated to 82.8 kPa, reproduced with permission from [137]. (C) Illustration of the contraction and pressure sensors, reproduced with permission from [137].…”
Section: Liquid-metal Microsphere Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] In this study, by taking advantage of the deformable feature of the soft robot, we estimate the high-dimensional but coupled states of the system using a single embedded proprioceptive soft sensor. [34][35][36][37] The concept of proprioception comes from biological muscle systems, where a muscular unit internally detects its stretch or stress by the embedded sensing elements inside, such as muscle spindles or Golgi tendon organs. [38,39] We first understand how the deformations (outputs) are distributed along the finger according to the state and then we suggest the estimation strategy based on the mapping from the state to the outputs.…”
Section: Introductionmentioning
confidence: 99%